2016
DOI: 10.1002/jmv.24459
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study of human parvovirus B19 infection in East China

Abstract: Human parvovirus B19 (B19V) infection causes a number of diseases in humans, and, in some circumstances, can be life threatening. To understand the epidemiology of B19V infection in the greater metropolitan area of Hangzhou, East China, we performed surveys of IgM and IgG antibodies against B19V and quantification of B19V DNA, by using enzyme-linked immunosorbent assay and quantitative PCR, respectively, in plasma samples from diverse groups. These groups included anemia patients, Mycoplasma pneumonia- and Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Indeed, according to data from the Ministry of Public Health, several outbreaks of measles-like rashes have occurred over the last 5 years in Katanga. As B19V IgM antibodies and DNA were found in sera from all provinces of DRC, it can be confirmed that B19V has spread countrywide, and this supports the hypothesis that B19V has a worldwide distribution ( Rezaei et al, 2016 , Zhang et al, 2016 , Toshev et al, 2014 , Tolfvenstam et al, 2000 , Schwarz et al, 1989 ).…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, according to data from the Ministry of Public Health, several outbreaks of measles-like rashes have occurred over the last 5 years in Katanga. As B19V IgM antibodies and DNA were found in sera from all provinces of DRC, it can be confirmed that B19V has spread countrywide, and this supports the hypothesis that B19V has a worldwide distribution ( Rezaei et al, 2016 , Zhang et al, 2016 , Toshev et al, 2014 , Tolfvenstam et al, 2000 , Schwarz et al, 1989 ).…”
Section: Discussionsupporting
confidence: 71%
“…In this study, using a real-time PCR assay, B19V nucleic acid was detected in 10% of persons infected with HIV-1. This prevalence was nearly similar to 7.1% rate in HIV1-infected drug users in Hangzhou (33), 13.1% rate in HIV1-positive cases in Iran (34), and almost twice in comparison with 4.5% rate in Sichuan, China (35).…”
Section: Discussionsupporting
confidence: 67%
“…B19V infection is common worldwide, showing regional epidemiological differences, with generally over one-half of the adult population having been exposed. The prevalence of B19V-specific antibodies in the population is age dependent, increasing from 2 to 20% in children Ͻ5 years old to 15 to 40% in children 5 to 18 years old and to 40 to 80% in the adult population, depending on both the assays used and the population (214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225). Seroprevalence, however, is much lower in some isolated areas, such as the Rodriguez Islands and among some Brazilian tribes, with adult seroprevalences of only 2 to 10% (226,227).…”
Section: Epidemiology Virus Prevalence and Transmissionmentioning
confidence: 99%